Preliminary Experience With SPECT/CT to Evaluate Periarticular Arthritis Progression and the Relationship With Clinical Outcome Following Ankle Arthrodesis. (April 2020) - DeSutter, Christopher; Dube, Vincent; Ross, Andrew; Boyd, Gordon; Morash, Joel; Glazebrook, Mark
Background: Single photon emission computed tomography combined with computed tomography (SPECT/CT) could potentially aid in diagnosing periarticular arthritis/activity and progression, facilitate effective treatment options, and evaluate the effect surgery has on the clinical outcome of patients with ankle arthritis. The goal of our study was to assess SPECT/CT activity in the ankle and periarticular joints before and after ankle fusion surgery and determine whether it was associated with clinical pain and function scores. Methods: Thirty-four patients recruited into this study underwent either arthroscopic or open ankle fusion. X-ray (XR) and SPECT/CT imaging was obtained as well as completion of patient Ankle Osteoarthritis Scale (AOS) and 36-item Short Form Survey (SF-36) questionnaires preoperatively and at 6 months postoperatively. Ankle, subtalar, and talonavicular joint arthritis grading on XR and CT, along with SPECT/CT activity, was evaluated by 2 nuclear medicine radiologists. Data were assessed for normality and analyzed with the appropriate comparative test. P value was set at <.05. Thirty patients (31 ankles) completed follow-up and were analyzed. Results: SPECT/CT activity showed no significant difference in the ankle joint at 6 months postoperatively while periarticular joint activity significantly increased ( P < .05). Six months postoperatively, patients had significant improvements in their AOS and SF-36 scores ( P < .05). SPECT/CT grading of all joints analyzed, however, was not associated with AOS or SF-36 scores preoperatively or at 6 months postoperatively. Conclusion: In this study, intensity of activity as evaluated by SPECT/CT in periarticular hindfoot joints in patients who had ankle arthrodesis was not associated with clinical/functional scores at 6 months postoperatively. Level of Evidence: Level IV, diagnostic study.